Financial Position of Transport Companies (Methodology and Methods for Analysis) - Ivanova, Rositsa (Research Papers, 2021)
The entity’s financial position is a complex term. It may be defined as status, composition, structure and dynamics of assets, liabilities and equity of the entity, as well as its ability to generate cash and cash equivalents with some level of certainty in timely manner that are necessary for meeting its obligations. The stable financial position is an objective prerequisite for the entity to continue its activity in foreseeable future.The aim of this report is to improve the methods for analysis of an entity’s financial position. The traditional methods for analysis are built-up by developing a system of indicators for analysis and assessment of the entity’s financial stability on the basis of which key criteria are determined. Meeting or failing to meet such criteria as a whole shows the level of financial stability or instability of the entity, respectively. On such basis the level of risk of insolvency or bankruptcy of the entity is analyzed and assessed. In this report the author tries to formulate an integrated approach for analysis of the entity’s financial position based on the logical unity between theory and practice.The object of this publication covers the financial position of the entity as an economic category and system. It interprets specific methodological and methodical issues with regard to the analysis of the financial position of a transport company.
Keywords: Methodology; Transport connectivity; Financial condition; Analysis; Factors